Audit of 62 cases of pancreatic resections for pancreatic cancer - Nichkaode, Prabhat; Bhukte, Shusrut; Bandhe, Aakash (International Surgery Journal, 2017)
Background: Varieties of pancreatic pathologies, needs resection of pancreatic tissue. Adenocarcinoma of the pancreatic duct is the most common malignancy presenting with early metastasis and seen as resistant to alternative treatment regimens currently available. Management and handling of such tumors is a complex and challenging task for a surgeon. Surgical resection offers an improved prognosis, with a median survival after resection of 14-20 months and up to 25% 5-year survival rates. Present study is aimed at presenting data of 62 pancreatic resections for various malignant pancreatic lesions. Methods: This is an ongoing longitudinal study which started in 2009 at teaching institute in central India. Though we had 109 patients for pancreatic resection, only 62 patients were considered suitable for the study. All patients after admission were thoroughly investigated and then considered for surgery. 48 patients were male and 14 patients were female. Age group was ranging from 33 to 65 years with mean age between 45 to 55 years. Spectrum of various malignancies and different types of pancreatic resections were done and results are presented here. Results: Pancreatic adenocarcinoma is an aggressive malignancy responds to surgical treatment better than other alternative modalities. In the present series out of 62 patients 27 patients with pancreatic head cancer, 22 patients with periampullary cancer, 2 patients with duodenal cancer, 6 patients with distal cholangio carcinoma, 1 patient with mucinous cystadenocarcinoma. 4 patients with body and tail of pancreas cancer. Average age 38 to 65 years, 47 males and 15 females. Commonest procedure was Whipple’s operation, and distal pancreatectomy. Survival in present series was 18 -24 months and 5-year survival was 12 % that is seen mainly with Periampullary cancer. Conclusions: Surgery is the only chance of cure or long-term survival in pancreatic cancer. Chemo radiation as a primary therapy is ineffective. But some reports suggest the improved quality of life with palliative chemotherapy. Biology of the disease is the king and dictates the survival, the type of surgical procedure had no impact on survival, nor on morbidity and mortality.